Gain clamping in L-band erbium-doped fiber amplifier using a fiber Bragg grating - Harun, Sulaiman Wadi; Low, S.K.; Poopalan, Prabakaran; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2002)
A gain-clamping technique for the long wavelength band (L-band) erbium-doped fiber amplifier (EDFA) is presented. It uses a single fiber Bragg grating (FBG) on the input side of erbium-doped fiber (EDF) to inject a portion of backward conventional band (C-band) amplified spontaneous emission (ASE) back into the system. The use of a narrow-band (NB) FBG has shown a better performance in clamped-gain level and noise figure compared to a broad-band FBG. The amplifier gain for the NB FBG set up is clamped at 15.4 dB with a variation of less than 0.3 dB for an input power as high as 0 dBm.